The Fulfilment of The Right to Education For Children Conflict With The Law In Indonesia in The Perspective Of Regulator and Implementation - Tuasela, Bernadus Alfons; Kristiawanto, Kristiawanto; Rattanapun , Supot (CV. Era Digital Nusantara, 2025)
The right to education is a human right guaranteed nationally and internationally, including for children in conflict with the law. This study aims to analyse the legal arrangements and implementation of the fulfilment of the right to education for children in Special Development Institutions for Children (LPKA) in Indonesia, and provide recommendations for reconstructing more effective policies. A normative juridical approach is used to examine relevant regulations, such as Law No 11/2012 on the Juvenile Criminal Justice System (SPPA Law) and Law No 2222 on Corrections, with a comparison of international practices in Malaysia and Japan. The results show a significant gap between legal arrangements and implementation. Education in LPKA is still limited to non-formal programmes due to a lack of infrastructure, teaching staff, and coordination between related institutions. To overcome this, a revision of the SPPA Law, strengthening educational infrastructure, improving the competence of teaching staff, and adapting international practices integrated with skills training are needed. In addition, anti-stigma campaigns and better monitoring mechanisms are needed to support children's reintegration into society. These measures are expected to not only guarantee the right to education, but also strengthen the rehabilitation and future of children in conflict with the law..